Leveraging culturally-relevant urban social housing to address Indigenous youth homelessness and transitions out of government care - Morton, Darrien; Conlon, Quinn; Delorme, Quinton; Pierce, Alex; Rieu, Jacqueline; Terrain, Rafael

(untitled) - Hatala, Andrew (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
Indigenous children and youth are overrepresented in settler-colonial child protection systems globally. They experience higher rates of homelessness and housing precarity when leaving care and searching for family and a place to call home. Missing from Canadian policy and research discussions is the role social housing can play to address these realities by providing a social safety net for permanent low-barrier housing. In this article, we highlight a community-based Solutions Lab that analyzed discursive policy constructions of ‘youth transition’ and explored the implications of austerity-driven social housing reform in a mid-sized metropolitan Canadian city. We illustrate potential challenges and opportunities for leveraging social housing by state governments and private markets which mediate housing precarity, belonging, and cultural conceptions of home.